2020
DOI: 10.1177/1049732320971236
|View full text |Cite
|
Sign up to set email alerts
|

“Taking Up a New Problem”: Context and Determinants of Pod-Mod Electronic Cigarette Use Among College Students

Abstract: In this article, we explore the context and determinants of pod-mod electronic cigarette (ECIG) use among college students aged 18 to 24 in the United States. We conducted semi-structured interviews with 55 students ( M age = 20 years, 56% female, 65% White) on three campuses in the Northwest, Midwest, and Southeast. We performed a thematic analysis. Students described ECIG use by peers, increased ECIG exposure and prevalence in college, and school-related stress as reasons for vaping. Pod-mod features such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Kava et al (2021) found a similar result of the college experience being a factor influencing college students to use e-cigarettes; they conducted a qualitative descriptive study with 55 college students (18–24 years old) who were recruited from three college campuses in the Northwest, Midwest, and Southeast. However, what this current study found with most participants that was not found previously in the literature was uncovered using the theoretical framework of RAM, which looks at the environment and how the college student adapts or maladapts to their environment.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Kava et al (2021) found a similar result of the college experience being a factor influencing college students to use e-cigarettes; they conducted a qualitative descriptive study with 55 college students (18–24 years old) who were recruited from three college campuses in the Northwest, Midwest, and Southeast. However, what this current study found with most participants that was not found previously in the literature was uncovered using the theoretical framework of RAM, which looks at the environment and how the college student adapts or maladapts to their environment.…”
Section: Discussionmentioning
confidence: 92%
“…The first theme encompassed the college experience: Most college students faced pressure and anxiety from dealing with COVID at this time as well as learning to deal with challenges of growing into adulthood, becoming independent, assuming a new identity in college, and balancing essential roles. Kava et al (2021) found a similar result of the college experience being a factor influencing college students to use e-cigarettes; they conducted a qualitative descriptive study with 55 college students (18-24 years old) who were recruited from three college campuses in the Northwest, Midwest, and Southeast. However, what this current study found with most participants that was not found previously in the literature was uncovered using the theoretical framework of RAM, which looks at the environment and how the college student adapts or maladapts to their environment.…”
Section: Discussionmentioning
confidence: 92%
“…For young adults who attend college, college's unique social environment may promote substance use, including e-cigarette use, through social network influence 3 and (mis)perceived norms of substance use among peers 4 . Indeed, college students report that friends influence their e-cigarette initiation 5 , report commonly using e-cigarettes with others and at social occasions 6 , and perceive high acceptability of e-cigarette use among peers 5,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Work conducted to date suggests that many adolescent and young adult e-cigarette users report an interest in quitting vaping (43-85%) and have attempted to do so (25-67%) [19][20][21][22][23][24][25][26]. Several factors have been found to be associated with quitting-related intentions and behaviour among young people, including (i) perceiving e-cigarette use to be harmful to health and likely to lead to dependence [20,21,27], (ii) being concerned about the health and addiction risks associated with e-cigarette use [22,23,[28][29][30][31], (iii) disapproval of use by important others [22,31,32], (iv) absence of use among family and friends [20,27], (v) having limited access to e-cigarettes [29],…”
Section: Introductionmentioning
confidence: 99%
“…Work conducted to date suggests that many adolescent and young adult e‐cigarette users report an interest in quitting vaping (43–85%) and have attempted to do so (25–67%) [19–26]. Several factors have been found to be associated with quitting‐related intentions and behaviour among young people, including (i) perceiving e‐cigarette use to be harmful to health and likely to lead to dependence [20, 21, 27], (ii) being concerned about the health and addiction risks associated with e‐cigarette use [22, 23, 28–31], (iii) disapproval of use by important others [22,31,32], (iv) absence of use among family and friends [20, 27], (v) having limited access to e‐cigarettes [29], (vi) device cost [22, 28, 30, 31, 33] and (vii) exposure to anti‐vaping messages [21,34]. Results relating to gender are mixed, with some studies finding that men are more likely than women to report intentions to quit [20, 21] and others finding no difference [19, 25, 35].…”
Section: Introductionmentioning
confidence: 99%